Comparative study of three tests for stereopsis: TNO®, Stereo Acuity Test Fly® and StereoTAB® in students in higher school - Morais, Rúben (2022)
Stereopsis is the perception of depth based on retinal disparity. Global stereopsis depends on the process of random dot stimuli and local stereopsis depends on contour perception. The aim of this study was to correlate three stereopsis tests: TNO®, StereoTAB®, and Fly Stereo Acuity Test® and to study the sensitivity and correlation between them, using TNO® as the gold standard. Other variables such as a near convergence point, vergences, symptoms, and optical correction were correlated with the three tests. Forty-nine students from Escola Superior de Tecnologia da Saúde de Lisboa (ESTeSL), aged 18-26 years old were included. The stereopsis mean (standard-deviation-SD) values in each test were: TNO® = 87.04’’ ±84.09’’; FlyTest® = 38.18’’ ±34.59’’; StereoTAB® = 124.89’’ ±137.38’’. About the coefficient of determination: TNO® and StereoTAB® with R2=0.6 e TNO® and FlyTest® with R2=0.2. Pearson correlation coefficient shows a positive correlation between TNO® and StereoTAB® (r=0.784 with α=0.01). The Phi coefficient shows a strong and positive association between TNO® and StereoTAB® (Φ=0.848 with α=0.01). In the ROC Curve, the StereoTAB® has an area under the curve bigger than the FlyTest® with a sensitivity of 92.3% for 94.4% of specificity, so it means that the test is sensitive with good discriminative power.